Views of Selected Malaysian Muslim Academia on Extremism in Islam and Its Implications to Contemporary Da‘wah - Mohamed Saniff, Shereeza; Mat Akhir, Noor Shakirah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
Islam is a religion that advocates peace. The very word Islam is derived from its root to bring forth the meaning of submission. While there is that acknowledgment that Islam is a religion that advocates for peace, current depiction of extremism in Islam, at times suggest the exact opposite. Today, the term â€œextremismâ€ is usually associated with terror and aggression of Islam. This presents itself as a rising challenge to Islam today as it becomes the hindering block to contemporary daâ€˜wah. As such this article sets out to examine the standpoint from the perspective of selected Malaysian Muslim Academia on the term â€œextremismâ€ in Islam. It attempts to analyse the misunderstanding that is prevalent on the term â€œextremismâ€ within the Muslim society through the lenses of selected Malaysian Muslim intellectuals. For the collection of data, two phases were embarked upon. The first phase consisted of the empirical research whilst the second phase involved library research. The empirical research refers to the information received through the face-to-face semi-structured in-depth interviews to selected Malaysian Muslim Academia. For the empirical part of data collection the data obtained was systematically arranged through the qualitative approach. The data collected from the first phase (empirical research) and the second phase (library research) were analysed using the textual analysis method. The article has set out that information collected showed that that there exist two inclinations to the perception of â€œextremismâ€ among the selected Malaysian Muslim Academia which bears grave implications to the efficacy of contemporary daâ€˜wah.